DEVELOPMENT AND OPTIMIZATION OF ARNEBIN-1 LOADED THERMOSENSITIVE HYDROGEL FOR WOUND HEALING - GODGE, RAHUL; BARDE, KAILAS; PAWAR, ONKAR; DIGHE, SANTOSH (International Journal of Applied Pharmaceutics, 2025)
Objective: To develop and optimize an arnebin-1-loaded thermosensitive hydrogel for enhanced wound healing applications. Current wound dressing methods lack purposes such as proper moisture regulation and suitable antimicrobial properties combined with inadequate drug delivery systems and poor patient usage. The novel arnebin-1 containing thermosensitive hydrogel employs sustained drug delivery and antimicrobial functions to solve current wound dressing issues. Methods: A 3² full factorial design was employed to develop thermosensitive hydrogels using Poloxamer 407 and Pectin as key variables. Nine formulations were systematically evaluated through response surface methodology, optimizing critical parameters of gelling temperature and mucoadhesive strength. Comprehensive characterization included physicochemical properties, ex-vivo permeation, stability studies, and antimicrobial assessment against common wound pathogens (E. coli and S. aureus). Results: Among nine formulations, KF6 emerged as the optimal formulation through desirability function approach (desirability = 1.0), containing Poloxamer 407 (36% w/v) and Pectin (0.9% w/v). KF6 demonstrated ideal physiological gelation (34.6±0.3 °C), enhanced mucoadhesion (4156±204 dynes/cm²), and sustained drug release (95.4% over 12 h). The formulation exhibited superior drug permeation (flux: 152.68±4.58 µg/cm²/hr), significant antibacterial activity against S. aureus (16.8±0.9 mm) and E. coli (14.2±0.7 mm) and maintained stability for three months under various storage conditions. Conclusion: The optimized thermosensitive hydrogel presents a promising platform for clinical wound management, offering advantages of ease of application, sustained drug delivery, and significant antimicrobial activity. This novel formulation provides a potential alternative to conventional wound dressings, warranting further clinical investigation for translation into therapeutic applications.